Experimental and numerical study on sheet metal lateral bending with both ends fixed - Mohd Shahril, Mohd Hassan (2012)
The main aim of this study is to compare the buckling phenomenon of sheet metal strip under both ends fixed setting. This study begins with a literature study. It was followed by design and fabrication of test equipment for strip buckling test. Initial research works was on design the test rig using solidwork software. The fabrication test rig consists of four different buckling test conditions. In this thesis, experimental and numerical investigation was dedicated to both ends fixed. Using the fabricated test rig, experimental was conducted to determine displacement and strain of the buckle specimen. Data from experiment have been compared with numerical modeling using Abaqus software. The results show good agreement between experimental and numerical analysis.